Magnetic resonance imaging in cervical cancer: current opportunities of radiomics analysis and prospects for its further developmen - A. E. Solopova; J. V. Nosova; B. B. Bendzhenova (Акушерство, гинекология и репродукция)
Introduction. Due to the dynamic development of modern imaging technologies in recent years, much attention has been paid to radiomics particularly texture analysis. The complexity of clinically evaluated tumor procession in cervical cancer (CC) accounts for a need to expand knowledge on applying medical imaging technologies in oncologic diagnostics spanning from predominantly qualitative analysis to a multiparametric approach, including a quantitative assessment of study parameters.Aim: to analyze the literature data on the use of radiomics and image texture analysis in diagnostics and prediction of aggressiveness of oncogynecological diseases including СС.Materials and Methods. A 2016–2023 systematic literature search was carried out in the PubМed/MEDLINE, eLibrary, Scopus databases, NCCN, ESUR, ACR resources. All publications on radiomics and image texture analysis used in CC diagnostics and prediction were investigated, with queries for key words and phrases in Russian and English: «cervical cancer», «radiomics»,«texture analysis», «oncology». The study included full-text sources and literature reviews on the study subject. Duplicate publications were excluded.Results. The features and advantages of using radiomics and image texture analysis in CC diagnostics were summarized. The introduction of the radiomic approach has expanded the views on interpretation of medical imaging data. The radiomics-based parameters extracted from digital images revealed high informativeness in some studies that contribute to improving diagnostic accuracy as well as expanding opportunities for predicting therapeutic effectiveness in CC patients.Conclusion. Radiomics used in diagnostics of oncogynecologic diseases including СС is one of the promising actively developing areas of analysis in radiology that requires to be further investigated.